2022
DOI: 10.1007/s12672-022-00579-x
|View full text |Cite
|
Sign up to set email alerts
|

BAP1 in cancer: epigenetic stability and genome integrity

Abstract: Mutations in BAP1 have been identified in a hereditary cancer predisposition syndrome and in sporadic tumours. Individuals carrying familiar BAP1 monoallelic mutations display hypersusceptibility to exposure-associated cancers, such as asbestos-driven mesothelioma, thus BAP1 status has been postulated to participate in gene-environment interaction. Intriguingly, BAP1 functions display also a high degree of tissue dependency, associated to a peculiar cancer spectrum and cell types of specific functions. Mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 77 publications
0
7
0
Order By: Relevance
“…Moreover, as C. elegans has orthologs for BRCA1 and BRAD1 ( brc-1 and brd-1 , respectively) [ 51 , 52 ], our model would help to study the mechanisms of controversial functional links between BAP1 and the BRCA1-BRAD1 complex, which play a critical role in DNA repair and homologous recombination, both in mammals [ 13 ] and C. elegans [ 53 , 54 ]. Since inactivation of the proteasome by RNAi or use of inhibitors produces aberrant nuclei in C. elegans germline [ 43 , 50 ] and BAP1 has a regulatory function on ubiquitination of histones [ 55 ], genome instability would be the “hallmark of cancer” behind the BAP1 alterations. Interestingly, although the specific mechanism of carcinogenesis induced by asbestos in MPM is still unclear, it has been proposed that asbestos causes genome instability [ 56 ] and chromosomal segregation defects [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, as C. elegans has orthologs for BRCA1 and BRAD1 ( brc-1 and brd-1 , respectively) [ 51 , 52 ], our model would help to study the mechanisms of controversial functional links between BAP1 and the BRCA1-BRAD1 complex, which play a critical role in DNA repair and homologous recombination, both in mammals [ 13 ] and C. elegans [ 53 , 54 ]. Since inactivation of the proteasome by RNAi or use of inhibitors produces aberrant nuclei in C. elegans germline [ 43 , 50 ] and BAP1 has a regulatory function on ubiquitination of histones [ 55 ], genome instability would be the “hallmark of cancer” behind the BAP1 alterations. Interestingly, although the specific mechanism of carcinogenesis induced by asbestos in MPM is still unclear, it has been proposed that asbestos causes genome instability [ 56 ] and chromosomal segregation defects [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…A BAP1 mutation has been previously associated with increased levels of H3K27me3. 11 , 54 , 55 Although this finding is often reported, Campagne et al did not observe a global effect of BAP1 knockout on the overall levels of H3K4me2 and H3K27me3. 56 In our study, an increase of H3K27me3 was only observed in one of the BAP1-mutated cell lines.…”
Section: Discussionmentioning
confidence: 70%
“…Several findings have suggested a potential role for BAP1 in the carcinogenesis of numerous malignancies [ 32 , 33 , 34 , 35 ]. BAP1 is an oncosuppressor protein that acts as a deubiquitinase and is involved in gene expression and chromatin regulation [ 34 , 35 , 36 ]; it is commonly inactivated in mesotheliomas [ 7 , 37 , 38 , 39 , 40 ]. Germline BAP1 mutations underpin the BAP1 tumor predisposition syndrome (BAP1-TPDS).…”
Section: Discussionmentioning
confidence: 99%
“…Some recent studies have suggested that BAP1 mutations may interact with exposure to carcinogens, such as asbestos. This gene–environment interaction is a possible carcinogenic mechanism [ 34 , 36 , 41 , 42 ]. Therefore, we evaluated the frequency of asbestos-related and BAP1 syndrome-related malignancies among SPC patients.…”
Section: Discussionmentioning
confidence: 99%